2011
DOI: 10.1124/jpet.111.181727
|View full text |Cite
|
Sign up to set email alerts
|

Delayed Administration of Suramin Attenuates the Progression of Renal Fibrosis in Obstructive Nephropathy

Abstract: We recently showed that suramin treatment prevents the onset of renal fibrosis in a model of obstructive nephropathy induced by unilateral ureteral obstruction (UUO). In this study, we further assessed the effect of delayed administration of suramin on the progression of tubulointerstitial fibrosis. Mice were given a single dose of suramin at 20 mg/kg starting at day 3 of obstruction, and kidneys were harvested after an additional 7 or 14 days of obstruction. Suramin completely blocked further increase in expr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
22
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 33 publications
2
22
0
Order By: Relevance
“…Suramin was previously suggested to inhibit fibrotic and growth inhibitory actions of TGF-β 1 and inhibit renal fibrosis [13], [15], [19], [41]. In our study, we found that renal TGF-β 1 and phospho-SMAD-3 protein expressions were elevated in 9 and 17 week old diabetic mice when compared to respective non-diabetic control mice and this increase was more exaggerated in 17 week than 9 week diabetic mice.…”
Section: Discussionsupporting
confidence: 59%
“…Suramin was previously suggested to inhibit fibrotic and growth inhibitory actions of TGF-β 1 and inhibit renal fibrosis [13], [15], [19], [41]. In our study, we found that renal TGF-β 1 and phospho-SMAD-3 protein expressions were elevated in 9 and 17 week old diabetic mice when compared to respective non-diabetic control mice and this increase was more exaggerated in 17 week than 9 week diabetic mice.…”
Section: Discussionsupporting
confidence: 59%
“…Suramin was previously suggested to inhibit fibrotic and growth inhibitory actions of TGF-␤ 1 and inhibit renal fibrosis (Liu and Zhuang, 2011;Liu et al, 2011b;Korrapati et al, 2012). In our study, we found that delayed administration of suramin after the induction of diabetes inhibited renal TGF-␤ 1 expression and subsequent SMAD-3 activation in diabetic rats.…”
Section: Downloaded Fromsupporting
confidence: 63%
“…Hyperglycemia is also known to induce activation of mitogen-activated protein kinases (e.g., ERK1/2), the STAT-3 pathway, and/or G proteinmediated aberrant expression of ECM proteins (Marrero et al, 2006;Catania et al, 2007;Tan et al, 2007). These kinases participate in transcriptional up-regulation of collagen and fibronectin in DN (Suzuki et al, 2004;Pang et al, 2010;Liu et al, 2011b). Phosphorylation and subsequent activation of NF-B and STAT-3 were blocked by suramin in diabetic rat kidneys.…”
Section: Downloaded Frommentioning
confidence: 92%
“…Further, delayed administration of suramin was also effective in attenuating the progression of renal fibrosis in obstructive nephropathy [13]. Therefore, there is the potential clinical application of suramin as an anti-fibrotic treatment in patients with chronic kidney disease.…”
Section: Discussionmentioning
confidence: 99%